A STUDY ON THE INHIBITORY EFFECT OF MATRINE ON GASTRIC CANCER SGC-7901 CELLS - Song, Shimao; Zhu, Shengming; Zhang, Zhiguo; Mo, Zhengying; Ke, Qing; Luo, Zhiguo (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to investigate the antitumour mechanism of action of matrine by studying its inhibitory effect on gastric cancer SGC-7901 cells. SGC-7901 cells were chosen, and cell-killing capacity of matrine on gastric cancer SGC-7901 cells was determined using MTT assay and single PI staining assay. The results showed that matrine had an inhibitory effect on gastric cancer SGC-7901 cells, which was somewhat dose-dependent. The study concluded that matrine has a significant in-vitro inhibitory effect on SGC-7901 tumour cells, influences cell cycle of SGC-7901 cells, and induces their apoptosis.